Neurocognitive impact of different irradiation modalities for patients with grade I-II skull base meningioma: a prospective multi-arm cohort study (CANCER COG) - Lesueur, Paul; Joly, Florence; Clarisse, Benedicte; Lequesne, Justine; Stefan, Dinu; Balosso, Jacques; Lange, Marie; Thureau, Sebastien; Capel, Aurelie; Castera, Marie; Legrand, Berenice; Goliot, Nicolas; et al. (Radiation oncology, 2025)
Radiotherapy as a complement or an alternative to neurosurgery has a central role in the treatment of skull base grade I-II meningiomas. Radiotherapy techniques have improved considerably over the last two decades, becoming more effective and sparing more and more the healthy tissue surrounding the tumour. Currently, hypo-fractionated stereotactic radiotherapy (SRT) for small tumours and normo-fractionated intensity-modulated radiotherapy (IMRT) or proton-therapy (PT) for larger tumours are the most widely used techniques. It is expected a decrease of the risk of cognitive impairment with these modern techniques. However prospective data about cognitive long-term consequences of partial brain irradiation with SRT, PT, or IMRT remain very scarce to date.